2007
DOI: 10.1021/jp071731p
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Engineering on Industrial Diaryl Pigments Using Lattice Energy Minimizations and X-ray Powder Diffraction

Abstract: Diaryl azo pigments play an important role as yellow pigments for printing inks, with an annual pigment production of more than 50,000 t. The crystal structures of Pigment Yellow 12 (PY12), Pigment Yellow 13 (PY13), Pigment Yellow 14 (PY14), and Pigment Yellow 83 (PY83) were determined from X-ray powder data using lattice energy minimizations and subsequent Rietveld refinements. Details of the lattice energy minimization procedure and of the development of a torsion potential for the biphenyl fragment are give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Electron diffraction data can also be used to solve the crystal structures, even of organic compounds [35,36] A search for isostructural derivatives with a known crystal structure or at least an improved X‐ray powder pattern Prediction of crystal structures by global lattice‐energy minimisation with force‐field or quantum‐mechanical methods,[37,38] followed by simulation of the diffraction patterns to determine which of the predicted structures corresponds to the actual polymorph [39–43] …”
Section: Method: General Procedures For Structure Determination From Xmentioning
confidence: 99%
See 1 more Smart Citation
“…Electron diffraction data can also be used to solve the crystal structures, even of organic compounds [35,36] A search for isostructural derivatives with a known crystal structure or at least an improved X‐ray powder pattern Prediction of crystal structures by global lattice‐energy minimisation with force‐field or quantum‐mechanical methods,[37,38] followed by simulation of the diffraction patterns to determine which of the predicted structures corresponds to the actual polymorph [39–43] …”
Section: Method: General Procedures For Structure Determination From Xmentioning
confidence: 99%
“…[35,36] • A search for isostructural derivatives with a known crystal structure or at least an improved X-ray powder pattern • Prediction of crystal structures by global lattice-energy minimisation with force-field or quantum-mechanical methods, [37,38] followed by simulation of the diffraction patterns to determine which of the predicted structures corresponds to the actual polymorph. [39][40][41][42][43] Comparison of structure determination from powder data and single-crystal data…”
Section: Remarksmentioning
confidence: 99%
“…It was also found that the molecules pack together in inclined stacks [4e6]. This work was followed by an important study involving a determination of the crystal structures of PY12, PY13, PY14 and PY83 from X-ray powder data using lattice energy minimizations and subsequent Rietveld refinements [7]. PY12 crystallized in a herringbone arrangement with twisted biphenyl fragments.…”
Section: Introductionmentioning
confidence: 99%
“…Even a separate patent covering this new crystal structure can be applied for. In the dye industry the situation is comparable [4,5]. For these reasons a good knowledge about possible polymorphs is essential.…”
Section: Introductionmentioning
confidence: 99%